The immunity protection of intestine induced by pseudorabies virus del gI/gE/TK in piglets - Zhang, Yang; Xu, Lei; Tao, Qian; Liu, Zheyan; Wen, Jianhua; Xu, Tong; Lai, Siyuan; Ai, Yanru; Xu, Zhiwen; Zhu, Ling (Frontiers in Microbiology, 2024)
Compared to the classical strain of Pseudorabies virus (PRV), the PRV variant exhibits stronger transmissibility and pathogenicity, causing immense disasters for the global pig industry. Based on this variant, our laboratory has preliminarily constructed a modified pseudorabies virus with deletions in the gE/gI/TK genes. In this study, the protective efficacy of PRV XJ del gI/gE/TK against piglet intestinal damage was evaluated. The results demonstrated that piglets immunized with PRV XJ del gI/gE/TK exhibited alleviated intestinal damage caused by the PRV XJ variant strain. This included reduced viral load, suppressed inflammation, and maintenance of intestinal structure and function. Additionally, PRV XJ del gI/gE/TK also strongly activated the innate immune response in the intestines, increasing the expression of antiviral factor mRNA and the secretion of SIgA to counteract the attack of the PRV XJ variant strain.Our study indicates that PRV XJ del gI/gE/TK can inhibit intestinal damage caused by PRV XJ variant strain and activate the innate immune response in the intestines.